The efficacy of celebrity endorsement towards youngsters in purchase decisions / Syara Izreen Mohd Shahrir - Mohd Shahrir, Syara Izreen (Faculty of Business and Management, 2020)
Celebrity endorsement practice has become an effective marketing method for companies to communicate to customers about their products. The study's objective is to examine the impact of celebrity endorsement on the purchase decision of young people. Celebrity expertise, celebrity attractiveness and celebrity trustworthiness are the characteristics of celebrity endorsement included in this study. The study was carried out in Kuala Lumpur using convenience sampling, especially on the youngsters. Using a standardized questionnaire, data were obtained from 338 respondents and the findings were analysed using SPSS 25. The analysis showed that celebrity expertise, celebrity attractiveness and celebrity trustworthiness have a positive relationship with the purchase decision. Based on the observations, a range of recommendations were made for businesses and also for future research purposes in order to achieve better results.